Dialogical Ethical Leadership Management Tools: An Organizational Development Opportunity for Productive Efficiency - Silva Ordóñez, Catalina; Naranjo Gaibor, Aidé Oliva; Salazar Mera, Juan Eduardo (My University, 2022)
The objective of the research is to link dialogical ethical leadership with the improvement of organizational management, seeking to enhance productive efficiency in the performance of functions in jobs. The exercise of leadership must be inserted in the application of management models of skills, human talent and knowledge as a single unit to replace the traditional management model based on vertical hierarchical processes that produce bureaucratization of work. It is proposed to exercise argumentative ethical leadership in all jobs from an intensive communication dynamic, capable of recognizing the worker as a reward for efficient work. The research was developed under the hermeneutic-documentary approach, exercising an assessment and critical posture that aims to generate contributions to the wonderful world of managerial sciences. © 2022, Universidad del Zulia. All rights reserved.
Herramientas de gestión de liderazgo ético dialógico: una oportunidad de desarrollo organizacional para la eficiencia productiva